PENTINGNYA MEDIA PEMBELAJARAN DALAM SISTEM PEMBELAJARAN - Febi Anita Sari (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
One of the main components in a learning process is the existence of learning media. Learning media is a tool that can help teachers to convey learning material so that children can have interest and interest in the learning material presented. It's just that in using learning media, the teacher must be able to choose learning media that suits the material to be delivered and the teacher must also adapt to the character of his students in choosing learning media. Some teachers still do not understand how important it is to use learning media that is appropriate to learning so that learning does not feel monotonous and boring for students. Therefore, in this research the author uses the library research method to examine how important appropriate learning media is for the teaching and learning process. The results of the research state that appropriate learning media is very important in supporting student learning. Choosing the right lesson can help students understand the learning material presented by the teacher. Learning media can provide concrete experiences and also act as intermediaries that help student learning.